Pengaruh Keterlibatan Pengguna pada Efektivitas Penggunaan SIA dengan Kapabilitas Personal Sistem Informasi Sebagai Variabel Pemoderasi - Baskara, Ida Bagus; Ary Wirajaya, I Gde (E-Jurnal Akuntansi; Vol 28 No 2 (2019)DO - 10.24843/EJA.2019.v28.i02.p14, 2019)
This study aims to determine the effect of user involvement on the effectiveness of the use of accounting information systems and to determine the personal capabilities of information systems in moderating the influence of user involvement on the effectiveness of using accounting information systems at PT. Bali Regional Development Bank. The number of respondents used in this study were 52 people who served as executors in the Information and Accounting Technology (TIA) section. Data collection is done by survey method with data collection techniques used in the form of questionnaires. Data analysis techniques were carried out using moderation regression analysis. The results of the study show that user involvement supported by the personal capabilities of information systems is able to increase the effectiveness of the use of accounting information systems at PT. Bali Regional Development Bank. Keywords: User involvement, SIA, personal capabilities of information system.